2016
DOI: 10.1007/s10971-016-4114-0
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of natural rubber/nitrile rubber blends by sol–gel nano-silica generated by in situ method

Abstract: Controlled growth of in situ silica, into natural rubber (NR)/nitrile rubber (NBR) blend (40/60 composition by weight) following solution sol-gel method, results in a coherent blend morphology with enhanced composite properties. Similar composites, i.e., in situ silica-filled NR/ NBR blend (40/60 by weight), showed better mechanical properties than any other composition that were prepared by soaking sol-gel method in earlier study. However, silica content in the rubber blend was limited to 20 phr (parts per hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 50 publications
2
22
0
Order By: Relevance
“…The NR/NBR vulcanizates without MBS showed typical rubber phase separation (Figure 7b) due to poor interfacial adhesion between the NR and NBR phase resulting from dissimilar polarity (Angnanon et al, 2011). Two distinct phases, NR (black) and NBR (gray), indicate the immiscibility of the components in the blends (Bansod et al, 2016). The rubber blends with MBS show that there is no phase separation identified on the tensile fracture surface of the NR/NBR blends (Figures 7(c)-(h)).…”
Section: Morphological Observationmentioning
confidence: 99%
“…The NR/NBR vulcanizates without MBS showed typical rubber phase separation (Figure 7b) due to poor interfacial adhesion between the NR and NBR phase resulting from dissimilar polarity (Angnanon et al, 2011). Two distinct phases, NR (black) and NBR (gray), indicate the immiscibility of the components in the blends (Bansod et al, 2016). The rubber blends with MBS show that there is no phase separation identified on the tensile fracture surface of the NR/NBR blends (Figures 7(c)-(h)).…”
Section: Morphological Observationmentioning
confidence: 99%
“…Firstly, it is of significance to modify silica to improve its dispersibility in the rubber matrix, and many related studies have been conducted. [15][16][17][18][19][20] For example, silica modified by silane coupling agents, [21][22][23][24][25][26] surfactant, [27][28][29][30] both silane coupling agents and surfactant, [31] grafting polymer, [32,33] adding other fillers, [34][35][36] ionic liquid. [37] What's more, mechanical force can also improve the dispersibility of silica, but it has little effect on the enhancement of interface strength due to the bad compatibility of silica and rubber.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, silica modified by silane coupling agents was a more extensive approach in which some hydroxyl groups on the surface of silica are grafted by the organic group of silane coupling agent. [21][22][23][24][25] This kind of partially organic structure can not only help the dispersibility of silica, but also enhance the interface adhesion between silica and rubber. But silane coupling agent is usually mixed with silica and rubber through the mechanical blending method, which is inefficient and need high temperature condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that the small amount of in situ silica could slightly reinforce the blends and reduced the flexibility of the rubber chains. This phenomenon was also observed for the reinforced NR, NR/nitrile rubber (NBR) blend and SBR modified by grafting with vinyltriethoxysilane (VTES) . To compare with rubber blends reinforced by using ex situ commercial silica at similar silica content, the Si‐EPDM/NR and Si‐HNR/NR vulcanizates showed slightly lower both TS and EB values than the in‐situ silica‐reinforced samples.…”
Section: Resultsmentioning
confidence: 70%